2013
DOI: 10.1186/1756-0500-6-326
|View full text |Cite
|
Sign up to set email alerts
|

Loss of genetic diversity and inbreeding in Kashmir red deer (Cervus elaphus hanglu) of Dachigam National Park, Jammu & Kashmir, India

Abstract: BackgroundHangul (Cervus elaphus hanglu), the eastern most subspecies of red deer, is now confined only to the mountains in the Kashmir region of Jammu & Kashmir State of India. It is of great conservation significance as this is the last and only hope for Asiatic survivor of the red deer species in India. Wild population of free ranging hangul deer inhabiting in and around Dachigam National Park was genetically assessed in order to account for constitutive genetic attributes of hangul population using microsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Mitochondrial markers had never been studied so far in this population, and their phylogenetic relationships were totally unknown. A microsatellite-based study has been published recently, revealing low genetic variability and high inbreeding for the population of Dachigam National Park, the last surviving nucleus of Kashmir red deer (Mukesh et al 2013). Based on our genetic results, this deer clearly belongs to the species C. hanglu (our nomenclature), although being distinct from Cervus hanglu bactrianus/Cervus hanglu yarkandensis (that are clearly synonyms), as suggested by a highly resolved node in the CR tree.…”
Section: Phylogenetic Analysis Of Cervus and Taxonomic Considerationssupporting
confidence: 63%
“…Mitochondrial markers had never been studied so far in this population, and their phylogenetic relationships were totally unknown. A microsatellite-based study has been published recently, revealing low genetic variability and high inbreeding for the population of Dachigam National Park, the last surviving nucleus of Kashmir red deer (Mukesh et al 2013). Based on our genetic results, this deer clearly belongs to the species C. hanglu (our nomenclature), although being distinct from Cervus hanglu bactrianus/Cervus hanglu yarkandensis (that are clearly synonyms), as suggested by a highly resolved node in the CR tree.…”
Section: Phylogenetic Analysis Of Cervus and Taxonomic Considerationssupporting
confidence: 63%
“…Out of 37 samples, 21 unique individuals were identified following Mukesh et al (2013b) where 7 females and 14 males were identified. Thus, all samples of known or unknown sexes were correctly assigned to their respective sexes.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the rigorous conservation efforts of the Department of Wildlife Protection in Jammu & Kashmir (J&K), the hangul population has experienced a severe decline in numbers and range contraction in the past few decades (Charoo et al 2010;Mukesh et al 2013b). The hangul population once abundant in the past has now largely confined to the Dachigam landscape, with a recent population estimate of 218 individuals (±13.96) in 2011 (Mukesh et al 2013b). It is listed under Schedule-I of the Indian Wildlife (Protection) Act, 1972 and J&K Wildlife (Protection) Act, 1978 and has also been categorized among the top 15 species of high conservation priority by the Government of India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, we collected 160 individual tufts of pneumatic hairs from different locations of the Dachigam NP. Details of sample collection and DNA extraction from hair samples have been presented elsewhere [ 15 ].…”
Section: Methodsmentioning
confidence: 99%